2016
DOI: 10.18632/oncotarget.8946
|View full text |Cite
|
Sign up to set email alerts
|

MiR-17-5p regulates cell proliferation and migration by targeting transforming growth factor-β receptor 2 in gastric cancer

Abstract: TGFBR2 serves as an initial regulator of the TGF-β signaling pathway, and loss or reduction of its expression leads to uncontrolled cell growth and invasion. TGFBR2 plays a crucial role in the carcinogenesis and malignant process of gastric cancer, but the mechanism remains unclear. In this study, we found that TGFBR2 protein levels were consistently upregulated in gastric cancer tissues, whereas TGFBR2 mRNA levels varied among these tissues, indicating that a post-transcriptional mechanism is involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…In addition, forced expression of miR-491-5p inhibited tumor proliferation, disrupted the cell cycle, and induced apoptosis in vitro and in vivo [49]. We also showed that lncRNA RP11-363E7.4 interacted with three miRNAs (miR-17-5p, miR-19b-3p, and miR-106a-5p), which were previously investigated in the reports of Xia et al, Zhang et al, and Qu et al [22,50,51]. …”
Section: Random Walk With Restart Analyses Of a Gc-related Lncrna-mrnsupporting
confidence: 65%
“…In addition, forced expression of miR-491-5p inhibited tumor proliferation, disrupted the cell cycle, and induced apoptosis in vitro and in vivo [49]. We also showed that lncRNA RP11-363E7.4 interacted with three miRNAs (miR-17-5p, miR-19b-3p, and miR-106a-5p), which were previously investigated in the reports of Xia et al, Zhang et al, and Qu et al [22,50,51]. …”
Section: Random Walk With Restart Analyses Of a Gc-related Lncrna-mrnsupporting
confidence: 65%
“…Because of the stability of miRNA, many studies regard it as a biomarker in human cancers, by acting as oncogenes or suppressors [23,24]. In various types of cancers, miRNA-related pathways is a heat-point, such as miR-17 and miR-29a/c in gastric cancer [25,26], miR-135b in colorectal cancer [27], miR-106a in cholangiocarcinoma [28]. MiRNAs are also related to development and progression of GC [29].…”
Section: Effects Of Egfr On Proliferation and Migration In Gc Cellsmentioning
confidence: 99%
“…Previous studies have demonstrated that expression levels of miRNAs are associated with cancer initiation and progression (15)(16)(17). The abnormal expression of miRNAs may suggest oncogenic or tumor suppressive functions of miRNAs in cancer, dependent on the tumor type and the target genes of the miRNA (18). Therefore, further studies on the regulatory mechanisms of miRNAs in cancer may provide an improved understanding of the oncogenes is network and potential therapeutic targets for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%